2018
DOI: 10.1016/j.jtcvs.2017.08.146
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative costs of video-assisted thoracoscopic lobectomy can be dramatically reduced without compromising outcomes

Abstract: The costs of VATSL differ substantially among surgeons and are heavily influenced by the use of disposable equipment/devices. Surgeons can substantially reduce the costs of VATSL to far lower than those of THORL without compromising surgical outcomes through prudent use of costly instruments and technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although we observed a lower cost for videothoracoscopic anatomic resections, the cost of VATS lobectomy was shown to be possibly further reduced through the prudent use of costly instruments and technologies. [9] Bendixen and colleagues performed a randomized study and reported that VATS is a cost-effective alternative to thoracotomy in stage 1 non-small cell lung cancer patients. [10] We were able to show that VATS is cost-effective in patients with stage IA-IIIA non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed a lower cost for videothoracoscopic anatomic resections, the cost of VATS lobectomy was shown to be possibly further reduced through the prudent use of costly instruments and technologies. [9] Bendixen and colleagues performed a randomized study and reported that VATS is a cost-effective alternative to thoracotomy in stage 1 non-small cell lung cancer patients. [10] We were able to show that VATS is cost-effective in patients with stage IA-IIIA non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the absence of documented Harmonic ACE Plus® greater impact on the surgical procedure and on postoperative short-term outcomes, electric hook may be preferred with the aim of saving direct cost of the energy device. However, ultrasonic device sealing ability could reduce the use of endoscopic staplers and ligating clips, that are also costly, and may impact on overall surgical costs [9,14,16,18,20].…”
Section: Discussionmentioning
confidence: 99%
“…It concludes that these choices are the main driver of cost variation between the 2 surgeons (whose outcomes were similar). 3 Despite the limited scope of this study, the concept of such comparisons is critical if we are soon to make judgments regarding the cost-effectiveness of robotics versus thoracoscopic thoracic surgery, or regionalizing some surgical procedures (such as esophagogastrectomy), or implementing other new technologies into surgical practice. The specific conclusions of this study are not as important as the process in which surgeons are aware of their own cost per case.…”
mentioning
confidence: 99%